Mathematical modeling of oxygen release from hyperbarically loaded polymers. (11th December 2018) - Farris, Ashley L.; Cook, Colin A.; Grayson, Warren L.
Abstract : Polymer‐based scaffolds are used extensively in the field of regenerative medicine. These biomaterials may induce therapeutic responses through modulating a wound microenvironment with or without the addition of cells. It has long been known that oxygen is a crucial component of the microenvironment that influences cellular and physiological processes such as metabolism, proliferation, differentiation, matrix deposition, phagocytic killing, and wound healing. Consequently, several studies have investigated the potential for using oxygen‐eluting biomaterials to regulate the oxygen tension within a wound microenvironment and to tune the regenerative response. We recently demonstrated that hyperbarically loaded polymers could be used as oxygen delivery devices for biomedical uses. To further develop this strategy, it is important to quantitatively characterize the spatiotemporal oxygen diffusion profile from scaffolds. Here, we use analytical and numerical solutions to describe the profiles of oxygen diffusion from hyperbarically loaded polymers as a function of different scaffold geometries, material compositions, and ambient temperatures. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 2018 © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2751, 2019.